IbM Pelatihan Pembuatan Tempe Higienis di Pusdiklat UNILAK - Hazra Yuvendius; Elvira Zondra; Yelmiza; Vonny Indah Sari (Universitas Lancang Kuning, 2022)
A training in the process of making tempeh is expected to be able to contribute to the economy, especially for students. At the beginning of the training, the average respondent did not know about the process of making tempeh, only 10% did. Whereas in question 2, it also has convenience but a little more level of knowledge. The difference between the level of knowledge of the participants was due to question 2 because they also received information from the media and the public. Furthermore, in questions 3 and 4, the average does not know at all. This is due to the absence of information about the processing technology, so the pre-test shows a tendency not to know the process of making tempeh, with an accumulation of ignorance below 30%, after the training is carried out, the level of students knowing the process of making tempeh is above 80% to 100%.